The Aspergillus flavus Phosphatase CDC14 Regulates Development, Aflatoxin Biosynthesis and Pathogenicity - Yang, Guang; Hu, Yule; Fasoyin, Opemipo E.; Yue, Yuewei; Chen, Lijie; Qiu, Yue; Wang, Xiuna; Zhuang, Zhenhong; Wang, Shihua (Frontiers in Cellular and Infection Microbiology, 2018)
Reversible protein phosphorylation is known to play important roles in the regulation of various cellular processes in eukaryotes. Phosphatases-medicated dephosphorylation are integral components of cellular signal pathways by counteracting the phosphorylation action of kinases. In this study, we characterized the functions of CDC14, a dual-specificity phosphatase in the development, septation, secondary metabolism and crop infection in of Aspergillus flavus. Deletion of AflCDC14 resulted in a nutrient-dependent growth defect and abnormal conidium morphology. Inactivation of AflCDC14 caused defective septum and failed failure to generate sclerotia. Additionally, the AflCDC14 deletion mutant (ΔCDC14) displayed increased sensitivity to osmotic and cell wall integrity stresses. Importantly, it had a significant increase in aflatoxin production, which was consistent with the up-regulation of the expression leves levels of aflatoxin biosynthesis related genes in ΔCDC14 mutant. Furthermore, seeds infection assays suggested that AflCDC14 was crucial for virulence of A. flavus. We It was also found that the activities activity of amylase was decreased in ΔCDC14 mutant. AflCDC14-eRFP mainly localized to the cytoplasm and vesicles during coidial germination and mycelial development stages. Taken together, these results not only reveal the importance of the CDC14 phosphatase in the regulation of development, septation, aflatoxin biosynthesis and virulence in A. flavus, but also may also provide a potential target for controlling crop infections of this fungal pathogen.